IN-DEPTH ANALYSIS OF FIGURATIVE LANGUAGE IN PINK'S "JUST GIVE ME A REASON" - Supeno, Supeno; Wibowo, Amiruddin Hadi; Ulfaika, Romlah; Priastuti, Dyah Nugraheny (Journal of Education and Research, 2024)
This article delves into the profound impact of figurative language in Pink's song "Just Give Me a Reason," unravelling the poetic brilliance that elevates music to new heights of emotional expression. Through a comprehensive analysis of metaphors, similes, symbolism, personification, apostrophe, synecdoche, metonymy, paradox, hyperbole, understatement, irony, alliteration, allusion, and onomatopoeia, the study reveals how Pink's masterful use of language creates a compelling lyrical landscape. Figurative language emerges as a powerful tool for artists to communicate complex emotions, foster vivid imagery, and forge deep connections with their audience. As listeners immerse themselves in this enchanting world, they embark on an emotional journey, experiencing the raw beauty of human experiences and the enduring power of artistic expression in the realm of music.